Parental psychological control and adolescent social problems: The mediating effect of emotion regulation - Qian, Guoying; Wu, Yufeng; Wang, Wei; Li, Lan; Hu, Xiaoyu; Li, Ruonan; Liu, Chunyu; Huang, Ao; Han, Ruiqi; An, Yu; Dou, Gang (Frontiers in Psychiatry, 2022)
This study aimed to investigate relationships among parental psychological control, adolescent emotion regulation, and social problems in China. In total, 1,145 adolescents aged 12–5 years participated in the study, which used the Parental Psychological Control Scale, Adolescent Problem Behavior Scale, and Emotion Regulation Scale. The results indicated the following: (1) Compared with only-child teens, adolescents in multi-child families had significant social problems; (2) parental psychological control significantly predicted adolescents' social problems; (3) there was a partially mediating effect of adolescents' emotion regulation between parental psychological control and adolescents' social problems.